Paternal Postnatal Psychiatric Illnesses A Clinical Case Book - Misri, Shaila Kulkarni (Springer International Publishing, 2018)
This book is the first to present the current research showing that like mothers, some fathers struggle with postpartum psychiatric illnesses and have unique needs of their own. Each chapter opens with a case vignette that describes different psychopathologies in the father and demonstrates the unique struggles presented by each situation. The cases highlight social, emotional and cultural upheaval that fathers may experience during the postpartum period. Sections in each chapter include manifestations of their illness, DSM-5 diagnoses, case discussion, treatment interventions and recommendations for health care professionals. This volume also puts paternal postpartum depression into conversation with other psychiatric comorbidities, including various personality disorders, anxiety disorders, and addictions. The text also addresses the various stigmas associated with these unique cases and offers clinical pearls on how to treat these families while giving consideration to the needs of the family. Written by renown experts in postpartum health, Paternal Postnatal Psychiatric Illnesses is an excellent resource for psychiatrists, psychologists, family therapists, general practitioners, obstetricians, social workers, and all clinicians working with postpartum families. .